Organoid models in lung regeneration and cancer. (10th April 2020) - Wang, Jianhai; Li, Xianglu; Chen, Huaiyong
Abstract: Improper regeneration is associated with lung diseases including lung cancer. Lung cancer is one of the leading causes of death worldwide, with nearly 2 million new cases diagnosed each year. The diagnosis is often too late for successful therapeutic intervention. Lung cancer shows substantial phenotypic and genetic heterogeneity between individuals, making it difficult to model in animals. Organoids, derived from regional stem/progenitor cells in lung epithelia, have attracted extensive interest in both research studies and the clinic, because of their great potential for use in cancer treatment. Various lung cancer organoids have been established to recapitulate the tissue architecture of primary lung tumors and maintain the genomic alterations of the original tumors during long-term expansion in vitro . In this review, we summarize the current data on lung epithelial regeneration by regional endogenous stem/progenitor cells, describe the development of organoid technology, and present its applications in lung cancer research. Furthermore, recent challenges and future directions to improve organoid technologies for lung cancer treatment are discussed. Highlights: Lung cancer originate from transformed epithelial cells in the lung. Lung epithelia are maintained by regional stem/progenitor cells. Lung stem/progenitor cells generate 3D organoids in vitro recapitulating the tissue architecture. Organoids can be exploited to model lung cancer and provide a platform for personalized cancer therapy.